Demand in New Zealand Hospitals: Expect the Unexpected? - Nan Jiang; Gail Pacheco (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2014)
The New Zealand health care sector stands out relative to other OECD countries, with relatively low per-capita health expenditure and a public dominant health system. Efficient allocation of resources is therefore paramount. This paper creates a predictive model for patient volume using the national database of hospital admissions. Contrasting predicted with actual demand, we construct indicators of volatility in unexpected demand (at the hospital and disease chapter level) and assess their role with regard to patient outcomes. There is consistent evidence that when actual exceeds predicted, patients stay in hospital longer, and are more likely to have an acute readmission.
Keywords: 330; hospital demand; emergency readmission; length of hospital stay